2015
DOI: 10.1016/j.tiv.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

PCB126 inhibits adipogenesis of human preadipocytes

Abstract: Emerging evidence indicates that persistent organic pollutants (POPs), including polychlorinated biphenyls (PCBs), are involved in the development of diabetes. Dysfunctional adipocytes play a significant role in initiating insulin resistance. Preadipocytes make up a large portion of adipose tissue and are necessary for the generation of functional mature adipocytes through adipogenesis. PCB126 is a dioxin-like PCB and a potent aryl hydrocarbon receptor (AhR) agonist. We hypothesized that PCB126 may be involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
5
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 69 publications
7
73
5
3
Order By: Relevance
“…In contrast, the induction of UCP1 mRNA by NE was significantly blunted with CGP treatment in mouse iWA (Figure 4C). In a third adipose cell culture model consisting of immortalized human subcutaneous preadipocytes (Gadupudi et al, 2015; Vu et al, 2013; Vu et al, 2015), we confirmed a suppressive effect of AT 2 activation upon UCP1 mRNA (Figure 4D). These data support an action of AT 2 receptors to modulate β-adrenergic signaling downstream of cAMP production and the bifurcation of second-messenger modulation of UCP1 expression versus lipolysis.…”
Section: Resultssupporting
confidence: 62%
“…In contrast, the induction of UCP1 mRNA by NE was significantly blunted with CGP treatment in mouse iWA (Figure 4C). In a third adipose cell culture model consisting of immortalized human subcutaneous preadipocytes (Gadupudi et al, 2015; Vu et al, 2013; Vu et al, 2015), we confirmed a suppressive effect of AT 2 activation upon UCP1 mRNA (Figure 4D). These data support an action of AT 2 receptors to modulate β-adrenergic signaling downstream of cAMP production and the bifurcation of second-messenger modulation of UCP1 expression versus lipolysis.…”
Section: Resultssupporting
confidence: 62%
“…The best characterized AhR agonists capable of eliciting effects in AT or adipocyte cell lines are TCDD and TCDD-like PCBs, which can be abolished by AhR antagonists (34) (121). Moreover, TCDD-induced impairment of adipogenesis in mouse embryonic fibroblasts was abolished when cells were isolated from AhR deficient mice (26).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…Reduced differentiation of 3T3-L1 cells to adipocytes by TCDD (71) (161) (320), PCBs (121), or DDT (278) was associated with decreased PPARγ gene expression. Further, TCDD suppressed PPARγ and adipogenesis via a MEK/ERK mechanism (79).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…PCB126 stimulated intrinsic changes in cell function by decreasing transcript levels of a key regulator of adipogenesis, PPARγ (Gadupudi, et al 2014). The ability of preadipocytes to mature is integral to development and homeostasis.…”
Section: Adipose Tissue and Pops Localizationmentioning
confidence: 99%
“…POP exposure compromising the ability of preadipocytes to differentiate in children and adolescents has the potential to alter their ability to form normal adipose tissue, ultimately leading to dysfunction and disease. In adults, chronic POPs exposure may alter their ability to replace mature adipocytes caused by cell death, again potentially leading to dysfunctional adipose tissue (Gadupudi et al 2014). …”
Section: Adipose Tissue and Pops Localizationmentioning
confidence: 99%